A meta‐analysis of the efficacy and safety of unboosted atazanavir compared with ritonavir‐boosted protease inhibitor maintenance therapy in HIV‐infected adults with established virological suppression after induction. Issue 5 (9th December 2013) - Baril, J; Conway, B; Giguère, P; Ferko, N; Hollmann, S; Angel, JB
<x xml:space="preserve">Abstract</x> Objectives Treatment simplification involving induction with a ritonavir (RTV)‐boosted protease inhibitor (PI) replaced by a nonboosted PI (i.e. atazanavir) has been shown to be a viable option for long‐term antiretroviral therapy. To evaluate the clinical evidence for this approach, we conducted a systematic review and meta‐analysis of randomized controlled trials (RCTs) evaluating efficacy and safety in patients with established virological suppression. Methods Several databases were searched without limits on time or language. Searches of conferences were also conducted. RCTs were included if they compared a PI/RTV regimen to unboosted atazanavir, after induction with PI/RTV. The meta‐analysis was conducted using a random effects model for the proportion achieving virological suppression (i.e. HIV RNA < 50 and <400 HIV‐1 RNA copies/mL), CD4 cell counts, lipid levels and liver function tests. Dichotomous outcomes were reported as risk ratios (RRs) and continuous outcomes as mean differences (MDs). Results Five studies (n = 1249) met the inclusion criteria. The meta‐analysis demonstrated no statistically significant difference in efficacy (i.e. HIV RNA < 50 copies/mL) between PI/RTV and unboosted atazanavir [RR = 1.04; 95% confidence interval (CI) 0.99 to 1.10], with no heterogeneity. Findings were similar in a subanalysis of studies where atazanavir/RTV was the only PI/RTV used during induction. Additional efficacy results support these findings. A significant reduction in total cholesterol (P < 0.00001), triglycerides (P = 0.0002), low‐density lipoprotein (LDL) cholesterol (P = 0.009) and hyperbilirubinaemia (P = 0.02) was observed with unboosted atazanavir vs. PI/RTV. Conclusions The meta‐analysis demonstrated that switching patients with virological suppression from an RTV‐boosted PI to unboosted atazanavir leads to improvements in safety (i.e. blood parameter abnormalities) without sacrificing virological efficacy.